Development of CRISPR/Cas9 system for targeted DNA modifications and recent improvements in modification efficiency and specificity - Shin, Juhyun; Oh, Jae-Wook (BMB reports, 2020)
The targeted nuclease clustered, regularly interspaced short palindromic repeats/CRISPR-associated proteins (CRISPR/Cas) system has recently emerged as a prominent gene manipulation method. Because of its ease in programming targeted DNA/protein binding through RNA in a vast range of organisms, this prokaryotic defense system is a versatile tool with many applications in the research field as well as high potential in agricultural and clinical improvements. This review will present a brief history that led to its discovery and adaptation. We also present some of its restrictions, and modifications that have been performed to overcome such restrictions, focusing specifically on the most common CRISPR/Cas9 mediated non-homologous end joint repair. [BMB Reports 2020; 53(7): 341-348].